Analisis Sifat Dasar Kepemimpinan Dan Gaya Kepemimpinan Transformasional Pada Ratu Jilbab (RJ): Studi Pada Pemimpin CV. Lyana Eka Pratama - Chanifa Jikhan, Fat'Chatus; Hermanto, Bambang; Wulan Tresna, Pratami; Hunafa Tajdida, Fityah (Program Studi Manajemen FEBM UMRAH, 2023)
This research aims to analyse the nature of leadership and transformational leadership style applied by Ratu Jilbab (RJ) leaders in the creative industry fashion subsector. The research method used is qualitative with descriptive analysis. The results showed that Ratu Jilbab (RJ) leaders have basic leadership traits such as motivation, empathy, self-esteem, decision making, commitment and interpersonal awareness. In addition, Ratu Jilbab (RJ) leaders also apply a transformational leadership style with four dimensions described in Bass' (1985) theory, namely idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration. Ratu Jilbab (RJ) leaders have basic leadership traits and all indicators for all four dimensions are fulfilled.